TRANSLATING VERBALLY EXPRESSED HUMOUR IN ASTERIX AND CLEOPATRA INTO SINHALA - Jayawardena, Samanthi (Selangor Humaniora Review, 2024)
The present study focuses on the translation of verbally expressed humour in dubbed animated films. The translators face the complex task of transferring humour from the source text to the target text. The study examines how they translate humorous elements and the strategies that they employ to perform this task. The animated film Asterix and Cleopatra (1968) and its Sinhala dubbed version are selected for the study. Humorous elements are identified and categorised into three groups, according to the taxonomy proposed by Minutella (2014): cultural references and allusions, wordplay and language variations. The Sinhala dubbed version is studied and ten examples are analysed qualitatively to understand how these elements are translated into the target language. The three strategies proposed by Chiaro (2006) are applied. The study reveals that the first strategy which is the substitution of verbally expressed humours in the source language with an example of verbally expressed humour in the target language, is employed mainly by the translators. The translation strategies employed are not always successful in transferring humour. Loss of humour, fully and partially, is noted in certain examples.